Bioinformatics and experimental insights into F2RL1 as a key biomarker in cervical cancer diagnosis and prognosis - Yonggang Dai; Chunxiang Li; Shiliang Cheng; Hongya Wang; Xuewei Zhuang (Scientific Reports)
Abstract Cervical cancer(CCa) remains a significant global public health concern, with early diagnosis and treatment being crucial. Moreover, the molecular mechanisms underlying its pathogenesis remain incompletely elucidated. F2RL1 is closely associated with various tumors. However, its relationship with CCa is poorly understood. We accessed data from 309 patients diagnosed with CCa from TCGA database. The Limma package facilitated differential expression analysis to identify differentially expressed mRNAs (DEmRNAs). Survival analysis and ROC analysis were conducted via the XIANTAO database. Immune-related genes were identified with F2RL1-related genes through ImmPort database analysis. Functional enrichment analysis was carried out using GO, KEGG, and GSEA. We gathered cervical cells and serum from participants to test for HPV and TCT, and then used qPCR to check the levels of F2RL1 mRNA expression. We also verified the expression of F2RL1 protein through WB and ELISA techniques. Our investigation has unveiled a fascinating discovery—the levels of F2RL1 expression in CCa tissues are notably elevated when compared to normal tissues, showcasing intriguing variations among various pathological types. Moreover, the presence of high F2RL1 expression is linked to reduce Overall Survival (OS), Progression Free Interval (PFI), Progression Free Survival (PFS). F2RL1 rocked the ROC analysis with an AUC of 0.996. Furthermore, F2RL1 expression levels significantly impact CCa in different N stages, pathological tissue types, treatment statuses, and racial groups, allowing us to develop a predictive model. Additionally, we identified 43 immune-related genes. Enrichment analysis highlighting their association with pathways related to cell movement and T cell activation. Through analysis, we discovered an inverse proportion between F2RL1 expression and the infiltration of most immune cells, particularly TFH and cytotoxic cells, suggesting a potential link to immune evasion in CCa. Molecular biology experiments also confirmed a significant increase in F2RL1 expression in cervical exfoliated cells and serum. Our research uncovers the predictive and early detection significance of F2RL1 in CCa and its correlation with immune infiltration for the first time. F2RL1 is strongly linked to the progression of CCa and could serve as a biomarker for the early diagnosis and prognosis of CCa patients.